Additive‐Induced Selective Crystallization of the Elusive Form‐II of γ‐Aminobutyric Acid. Issue 6 (7th May 2020) - Wang, Lingyu; Tang, Weiwei; Du, Shichao; Wu, Songgu; Gong, Junbo
Abstract: The impact of two structural factors of sodium carboxylate additives on their ability to induce the selective crystallization of γ ‐aminobutyric acid (GABA) Form‐II was investigated, namely, the number of –COO − groups and the types of R groups (chain alkyl, cyclic alkyl, or phenyl). It was found that the increase of –COO − groups caused the additives lose their inducing ability. This may be attributed to the fact that the increment of hydrophilic –COO − groups results in enhanced solvation and steric effect of additives, which makes additives unable to interact with GABA effectively. Additives with different R groups all can induce Form‐II but they exhibited varying inducing abilities. This could be due to the distinct results of competition between the attachment and detachment of different additives on the GABA growth end. Abstract : The strategy of additive‐induced polymorphs was applied to achieve selective crystallization of the elusive Form‐II of γ ‐aminobutyric acid. The effect of two structural factors of sodium carboxylate additives on their ability to induce such selective crystallization in terms of the number of –COO − groups and the types of the R group, i.e., chain alkyl, cyclic alkyl or phenyl, was evaluated.